Side-stream enhanced biological phosphorus removal (S2EBPR) process improves system performance - A full-scale comparative study. (15th December 2019) - Wang, Dongqi; Tooker, Nicholas B.; Srinivasan, Varun; Li, Guangyu; Fernandez, Loretta A.; Schauer, Peter; Menniti, Adrienne; Maher, Chris; Bott, Charles B.; Dombrowski, Paul; Barnard, James L.; Onnis-Hayden, Annalisa; et al.
Abstract: To address the common challenges in enhanced biological phosphorus removal (EBPR) related to stability and unfavorable influent carbon to phosphorus ratio, a side-stream EBPR (S2EBPR) process that involves a side-stream anaerobic biological sludge hydrolysis and fermentation reactor was proposed as an emerging alternative. In this study, a full-scale pilot testing was performed with side-by-side operation of a conventional anaerobic-anoxic-aerobic (A2O) process versus a S2EBPR process. A comparison of the performance, activity and microbial community between the two configurations was performed. The results demonstrated that, with the same influent wastewater characteristics, S2EBPR configuration showed improved P removal performance and stability than the conventional A2O configuration, especially when the mixers in the side-stream anaerobic reactor were operated intermittently. Mass balance analysis illustrated that both denitrification and EBPR were enhanced in S2EBPR configuration, where return activated sludge was diverted into the anaerobic zone to promote fermentation and enrichment of polyphosphate accumulating organisms (PAOs), and the influent was bypassed to the anoxic zone for enhancing denitrification. A relatively higher PAO activity and total PAO abundance were observed in S2EBPR than in A2O configuration, accompanied by a higher degree of dependence on glycolysis pathway than tricarboxylic acid cycle. No significant difference in the relative abundances of putative PAOs, including Ca. Accumulibacter and Tetrasphaera, were observed between the two configurations. However, higher microbial community diversity indices were observed in S2EBPR configuration than in conventional one. In addition, consistently lower relative abundance of known glycogen accumulating organisms (GAOs) was observed in S2EBPR system. Extended anaerobic retention time and conditions that generate continuous and more complex volatile fatty acids in the side-stream anaerobic reactor of S2EBPR process likely give more competitive advantage for PAOs over GAOs. PAOs exhibited sustained EBPR activity and delayed decay under extended anaerobic condition, likely due to their versatile metabolic pathways depending on the availability and utilization of multiple intracellular polymers. This study provided new insights into the effects of implementing side-stream EBPR configuration on microbial populations, EBPR activity profiles and resulted system performance. Graphical abstract: Image 1 Highlights: First full-scale investigation of S2EBPR versus conventional A2O configuration. Side-stream EBPR configuration improves P removal performance. S2EBPR has higher microbial diversity with lower known relative GAO abundance. S2EBPR has higher glycolysis activity than those in conventional A2O process. S2EBPR configuration provides competitive advantages for PAOs over GAOs.